1986
DOI: 10.1213/00000539-198609000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Diltiazem Levels, Cardiovascular Function, and Coronary Hemodynamics during Enflurane Anesthesia in the Dog

Abstract: KAPUR PA, CAMPOS JH, BUCHEA OC. Plasma diltjazem levels, cardiovascular function, and coronary hemodynamics during enflurane anesthesia in the dog. Anesth Analg 1986;65:918-24.Diltiazein 7ons ndininistered to dogs by a n intraueiious illfiisiori protocol, which resulted in plasma levels of 71 ? 6 ( I i = 7 ) , 139 ? 9 ( n = 7), 353 i 33 ( n = l o ) , and 1064 ? 143 (11 = 6) ng/ml, to ezialunte the effects of diltiazetn on i-nrrfiouasculur functioii mid coronar>y heinodynainics in the prescnce of mesthetic conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
2

Year Published

1988
1988
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
4
2
Order By: Relevance
“…The effects of diltiazem on the coronary circulation appear to vary with the baseline anaesthetic. In contrast to the results of this study, CVR did not change in dogs anaesthetized by isoflurane or enflurane [17,18].…”
Section: Coronary Circulationcontrasting
confidence: 99%
See 2 more Smart Citations
“…The effects of diltiazem on the coronary circulation appear to vary with the baseline anaesthetic. In contrast to the results of this study, CVR did not change in dogs anaesthetized by isoflurane or enflurane [17,18].…”
Section: Coronary Circulationcontrasting
confidence: 99%
“…In contrast to the preservation of global RV and LV function during fentanyl anaesthesia noted in this study, in the presence of volatile anaesthetics, diltiazem has been shown to be a potent myocardial depressant [10,17,18]. This might have been the result of absence of afterload reduction, underlying myocardial depression caused by inhalation anaesthetics or impaired baroreceptor reactivity.…”
Section: Diltiazem and Ventricular Performancecontrasting
confidence: 73%
See 1 more Smart Citation
“…The potential use of diltiazem in clinical anaesthesia may be limited by adverse electrophysiological effects, which occur at plasma concentrations necessary to achieve haemodynamic changes. Second degree AV block and junctional escape rhythm at plasma concentrations of less than 300 ng ml" 1 have been reported during enflurane [8] and isoflurane [5] anaesthesia in dogs. In the present study, during fentanyl-nitrous oxide anaesthesia, second degree AV block was not observed consistently until relatively high plasma diltiazem concentrations were achieved (greater than 400 ng ml" 1 ).…”
Section: Discussionmentioning
confidence: 98%
“…Studies undertaken at the cardiopulmonary research laboratory of the Department of Anesthesiology at the UCLA School of Medicine, have been related to various aspects of the cardiovascular interactions of newer cardioactive drugs with anaesthetics. These have included: arrhythmia studies with verapamil [6,7], comparison of the influence of the different inhalation anaesthetics upon verapamil pharmacodynamics [3], pharmacodynamic studies of diltiazem with varying anaesthetics [4,5], interactions of betaadrenergic blockers with verapamil comparing barbiturate with halothane anaesthesia [8,18], a series of studies related to the properties of the newer cardiotonic drug amrinone [11][12][13], and continuing studies of the cardiovascular relationships between local anaesthetic compounds and calcium channel blocking drugs.…”
mentioning
confidence: 99%